SOSIALISASI PERAN RADIOGRAFER DALAM BIDANG KESEHATAN DI SMA BAGAN SIAPI-API - Shelly Angella; Marido Bisra; Lili Wahyuni (Awal Bros Journal of Community Development, 2020)
Radiographer is health is health workers that have given duty, authority and responsibility by authorized official to do radiography and imaging activities in health sevice unit. Radiographer is health workers tat give contribution in radiography and imaging field in an attempt to rise the quality of health service.Lack of public knowledge about radiographer role especially in Rokan Hilir district. There is no devotion to students or society about radiology and radiographer role until 2020. Added with Radiology study program STIKes Awal Bros Pekanbaru is the only one in Riau, Kepri and Jambi take campus attention to give devotion to students for introduce and give understanding about radiology and radiographer. The aim of this devotion is to explain about definition from radiology and radiographer. Explain about medical radiographer role. Thie devotion implemented in Rokan Hilir district. The socialization is done by teacher and students SMA Negeri 1 Bangko Bagan Siapi-api. This devotion is done with extension way. Giving instruction to students about radiographer definition, function and scope of radiology. Explain about definition and many kinds of radiology examination.Give leaflets about medical radiographer. The devotion activities has been done in SMA Negeri 1 Bangko Bagan Siapi-api. All teachers, students that follow this activities has understand about radiographer role. They also understand about radiographer and radiology definition. This activities should give bigger chance to public. The devotion informer can socialization ith faster and wider